Anatomical and Morphological Changes with Needle Removal Treatments on the Seedlings of Pinus nigra Arn. (Anatolian black pine) - ÖZDEN KELEŞ, Seray (Bartin Orman Fakultesi Dergisi, 2020)
The effect of needle removal treatments on the morphology, anatomy and wood density was less studied in the literature. Therefore, the aim this study was to investigate the effect of needle removal on the morphological, anatomical and wood density properties of the seedlings of Pinus nigra Arn. (Anatolian black pine). The needles of the seedlings were removed in four different amounts (0%, 25%, 50% and 75%) to determine whether there is a relationship between the properties of seedlings and the needle removal treatments. The morphological (stem diameter, node numbers, pith percentage, bark percentage, xylem percentage), anatomical properties (average annual ring width, tracheid number per mm2, tracheid height/width, tracheid lumen width, tracheid wall thickness, ray number per mm2, ray height/width) and wood densities were individually determined for each treatment. The morphological results showed that stem diameter was greatest in 0% and 25% needle removal treatments than that of two treatments. Bark% was also found to be higher in the 0% needle removal treatments than others. However, node numbers, pith% and xylem% did not differ significantly between four removal treatments. The density results showed that the seedlings of 0% and 25% needle treatments were denser than 50% and 75% needle removal treatments. The results of anatomical analysis also found surprising results between four treatments. Ray height/width, tracheid number per mm2and tracheid length were significantly greater in the 0% removal of needles than that of three treatments. 25% needle removal treatment also showed larger tracheid area and tracheid wall thickness than that of three needle removal treatments.
Keywords: Morfoloji; Odun Anatomisi; İbre eksiltme; Çam fidanları; Yoğunluk; Forest Industry Engineering; Morphology; Wood Anatomy; Needle removal; Pine seedling; Density; Orman Endüstri Mühendisliği